2021
DOI: 10.1002/celc.202101223
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial pH Measurements Using a Rotating Ring‐Disc Electrode with a Voltammetric pH Sensor

Abstract: Dedicated to Professor Wolfgang Schuhmann on the occasion of his 65 th birthday and his eminent contributions to physical and analytical electrochemistry.Electrochemical reactions in which H + or OH À ions are produced or consumed, affect the pH near the electrode surface. Probing the pH locally is therefore highly desired to understand and model the reaction environment under operando conditions. We carried out interfacial pH measurements under mass transport control using a rotating ring-disc electrode (RRDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…have shown that for low current densities (<4.33 mA/cm 2 at 1600 rpm) no significant local pH changes are observed. On the other hand, recent experiments in our group have shown that even at relatively low current densities, the local pH at rotating electrodes can be significantly different from the bulk pH [62] . However, as the change in bulk pH and buffer capacity are minor, we do not expect the pH to dominate the temperature effect observed in Figure 1.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…have shown that for low current densities (<4.33 mA/cm 2 at 1600 rpm) no significant local pH changes are observed. On the other hand, recent experiments in our group have shown that even at relatively low current densities, the local pH at rotating electrodes can be significantly different from the bulk pH [62] . However, as the change in bulk pH and buffer capacity are minor, we do not expect the pH to dominate the temperature effect observed in Figure 1.…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, recent experiments in our group have shown that even at relatively low current densities, the local pH at rotating electrodes can be significantly different from the bulk pH. [62] However, as the change in bulk pH and buffer capacity are minor, we do not expect the pH to dominate the temperature effect observed in Figure 1. The local pH can change because the current densities are higher, but this is then the result of the increased activity, instead of the cause.…”
Section: Chemelectrochemmentioning
confidence: 64%
“…Phosphate-mediated HER (Figure 1a, black dashed lines) is observed as a mass-transfer limited peak at potentials less cathodic than water dissociation (Figures S1 and S2), where protons are easier to extract from phosphate anions than from water. 31 The comparable mass-transfer limited current density (ca. 2 mA/cm geo 2 ; Figure S1) across TMs indicates similar roughness (ratio of actual and geometric surface areas) except for the lower-roughness Ag and Co.…”
Section: Role Of H Chemisorptionmentioning
confidence: 99%
“… 8 The RRDE ring electrode can also be used as a pH sensor to detect pH changes resulting from reactions on the disk. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%